2016
DOI: 10.2969/jmsj/06810245
|View full text |Cite
|
Sign up to set email alerts
|

Restriction de la représentation de Weil à un sous-groupe compact maximal

Abstract: Dans cet article nous démontrons que la représentation de Weil sur un corps p-adique avec p = 2 restreinte à un sous-groupe compact maximal ou un tore maximal elliptique du groupe métaplectique se décompose sans multiplicité et décrivons explicitement les représentations irréductibles ou les caractères qui interviennent.Mots clés: représentation de Weil, groupe métaplectique, sous-groupe compact maximal, tore maximal elliptique 1991 MSC: 22E50 Abstract: In this article, we prove that the restriction of the Wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…-Any F -distinguished orbit is quasi-admissible, since for such orbits M γ is trivial. Over non-Archimedean F , F -distinguished orbits are admissible since the metaplectic cover splits over compact subgroups, see [38,Theorem 4.6.1]. Over F = R, the minimal orbit in U (2, 1) is Rdistinguished but not admissible.…”
Section: Proof Of Theorem 13mentioning
confidence: 99%
“…-Any F -distinguished orbit is quasi-admissible, since for such orbits M γ is trivial. Over non-Archimedean F , F -distinguished orbits are admissible since the metaplectic cover splits over compact subgroups, see [38,Theorem 4.6.1]. Over F = R, the minimal orbit in U (2, 1) is Rdistinguished but not admissible.…”
Section: Proof Of Theorem 13mentioning
confidence: 99%
“…Any F -distinguished orbit is quasi-admissible, since for such orbits M γ is trivial. Over non-Archimedean F , F -distinguished orbits are admissible since the metaplectic cover splits over compact subgroups, see [MT16]. Over F = R, the minimal orbit in U (2, 1) is Rdistinguished but not admissible.…”
Section: Proof Of Theorem Bmentioning
confidence: 99%
“…A small part of the decomposition has been explained in the general case (Cliff-McNeilly-Szechtman [4]). In their paper [14], Maktouf and Torasso have shown that the restriction of the Weil representation of a symplectic group over a p-adic field to a maximal compact subgroup or to a maximal elliptic torus is multiplicity-free and have given an explicit description of the irreducible subrepresentations.…”
mentioning
confidence: 99%